Antibiotic exposure for culture-negative early-onset sepsis in late-preterm and term newborns an international study - Dimopoulou Varvara (PEDIATRIC RESEARCH, 2025)
Early-life antibiotic exposure is disproportionately high compared to the burden of culture-proven early-onset sepsis (CP-EOS). We assessed the contribution of culture-negative cases to the overall antibiotic exposure in the first postnatal week.We conducted a retrospective analysis across eleven countries in Europe, North America, and Australia. All late-preterm and term infants born between 2014 and 2018 who received intravenous antibiotics during the first postnatal week were classified as culture-negative cases treated for ≥5 days (CN ≥ 5d), culture-negative cases treated for <5 days (CN < 5d), or CP-EOS cases.Out of 757,979 infants, 21,703 (2.9%) received intravenous antibiotics. The number of infants classified as CN ≥ 5d, CN < 5d, and CP-EOS was 7996 (37%), 13,330 (61%), and 375 (1.7%). The incidence of CN ≥ 5d, CN < 5d, and CP-EOS was 10.6 (95% CI 10.3-10.8), 17.6 (95% CI 17.3-17.9), and 0.49 (95% CI 0.44-0.54) cases per 1000 livebirths. The median (IQR) number of antibiotic days administered for CN ≥ 5d, CN < 5d, and CP-EOS was 77 (77-78), 53 (52-53), and 5 (5-5) per 1000 livebirths.CN ≥ 5d substantially contributed to the overall antibiotic exposure, and was 21-fold more frequent than CP-EOS. Antimicrobial stewardship programs should focus on shortening antibiotic treatment for culture-negative cases.In a study of 757,979 infants born in high-income countries, we report a presumed culture-negative early-onset sepsis incidence of 10.6/1000 livebirths with an associated antibiotic exposure of 77 antibiotic days per 1000 livebirths. This study sheds light on the major contribution of presumed culture-negative early-onset sepsis to early-life antibiotic exposure. Given the diagnostic uncertainty surrounding culture-negative early-onset sepsis, the low mortality rate, and the disproportionate antibiotic exposure associated with this condition, our study emphasizes the importance of targeting culture-negative early-onset sepsis in antimicrobial stewardship programs.